2018
DOI: 10.31689/rmm.2018.25.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Withdrawal Syndrome: a Review

Abstract: Alcoholism is a common condition and frequently clinicians are forced to confront its complications in general hospital settings. There are an estimated 3 million alcohol-dependent people in Romania alone, from which a significant number suffers episodes of withdrawal severe enough to require pharmacologic treatment. Alcohol withdrawal syndrome is a clinical diagnosis, with symptoms that range from minor (anxiety/palpitations) to severe (delirium tremens/hallucinations). Benzodiazepines have the best evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Cronicitatea, tendinţa de suicid, nevoia de psihoterapie şi cantitatea antidepresivelor utilizate determină medicii de familie să trimită pacienţii depresivi către specialist (22,23,24,25).…”
Section: Figura 1 Abordarea Pacientului Cu Depresieunclassified
“…Cronicitatea, tendinţa de suicid, nevoia de psihoterapie şi cantitatea antidepresivelor utilizate determină medicii de familie să trimită pacienţii depresivi către specialist (22,23,24,25).…”
Section: Figura 1 Abordarea Pacientului Cu Depresieunclassified
“…As for the alcohol consumption, there are mixed observations reported, some studies showing a correlation between the risk of developing and progression of chronic kidney disease and the increased alcohol consumption [27][28][29] . However, most studies have not found a significant link between moderate alcohol consumption and the progression of chronic kidney disease 30,31 .…”
Section: Other Nutritional Modelsmentioning
confidence: 99%